ISSUES OF SPIRITUALITY IN THE STATE OF AMIR TEMUR (American Journal of Interdisciplinary Research and Development, 2023)
In this article, based on sources and monographs, the personality of Amir Timur and his attitude to such concepts as loyalty, courage and decency are analyzed. friendship, justice. The examples show how Timur was far from fanaticism and sectarianism, was tolerant in religion and fair in his decisions.